PENGUATAN LITERASI QUR’ANI MASYARAKAT MELALUI PENDAMPINGAN BACA TULIS ALQUR’AN BERBASIS MASJID DAN EVALUASI BERKELANJUTAN - Tamrin Talebe; Sawaluddin Siregar; Idham Chalid Erwandha (Yayasan Baitul Hikmah al-Zain, 2026)
Strengthening Qur’anic literacy in the community is a strategic effort to enhance the ability to read, write, and understand the Qur’an accurately, sustainably, and contextually. This community service activity was conducted through mosque-based guidance for reading and writing the Qur’an, supported by continuous evaluation, targeting local communities with limited access to Qur’anic education. The approach included intensive learning, personalized mentoring, repetitive practice, and routine monitoring by instructors and mosque administrators. Data were collected through direct observation, daily participant evaluation records, interviews with participants and mosque officials, and documentation of learning activities. Data were analyzed descriptively and qualitatively to assess literacy improvement, participation levels, emerging challenges, and the effectiveness of continuous evaluation. The results indicate significant improvement in participants’ Qur’anic reading and writing skills, heightened awareness of the importance of consistent practice, and increased motivation to continue learning through mosque-based guidance. Continuous evaluation proved effective as a monitoring tool, providing feedback and informing follow-up program planning. Active involvement of mosque administrators, instructors, and community members was identified as a key factor for the program’s success. This service model demonstrates that integrating community-based guidance with ongoing evaluation can be an effective strategy to build consistent, inclusive, and sustainable Qur’anic literacy in local communities.